Elevasi Kaki Efektif Menjaga Kestabilan Tekanan Darah pada Pasien dengan Spinal Anastesi - I Made Sukarja (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2015)
The aim of this study is to explore the effect of foot elevation to the blood pressure of the patients with spinal anesthetic. The study design was pre-experimental with static group comparison. 30 samples was chosen by consecutive sampling, 15 samples as control group and 15 samples as experiment group. Result of this study showed the difference of blood pressure before and five minute after spinal anesthetic. Mann-Whitney statistical test was used to analyse the hypothesis of Systolic Blood Pressure mean differences. Independent T-Test was used to analyse Diastolic Blood Pressure and Mean Arterial Pressure mean difference. The result show that the p value was 0,001 for SBP, 0,000 for DBP and 0,000 for MAP. The conclusion shows that there was the significant effect of foot elevation to the blood pressure for spinal anesthetic patients at operating theater Sanglah hospital.